Autonomous vehicles in the response to maritime incidents - João B. Sousa (2008)
The future role of autonomous vehicles in the emergency response to maritime incidents is discussed and a framework for their integration into existing response plans is proposed. This is done in the context of the developments on autonomous vehicle systems from the Underwater Systems and Technologies Laboratory from Porto University.